2017
DOI: 10.1126/sciadv.1602312
|View full text |Cite
|
Sign up to set email alerts
|

Observation of inverse Edelstein effect in Rashba-split 2DEG between SrTiO 3 and LaAlO 3 at room temperature

Abstract: Gate-tunable inverse Edelstein effect is observed at room temperature in Rashba-split 2DEG at the complex oxide interface.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
119
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 152 publications
(127 citation statements)
references
References 48 publications
4
119
1
Order By: Relevance
“…Finally, when the chemical potential enters the d xz d yzbands we obtain a sizable SGE response and the overall behavior is in very good agreement with the gate voltage dependence of the spin galvanic effect as measured in Ref. [16] at T = 300 K. In contrast, the voltage dependence of the SGE response in Ref. [15] has been measured at much lower temperature T = 7 K and shows the sign change upon voltage reversal.…”
supporting
confidence: 85%
See 2 more Smart Citations
“…Finally, when the chemical potential enters the d xz d yzbands we obtain a sizable SGE response and the overall behavior is in very good agreement with the gate voltage dependence of the spin galvanic effect as measured in Ref. [16] at T = 300 K. In contrast, the voltage dependence of the SGE response in Ref. [15] has been measured at much lower temperature T = 7 K and shows the sign change upon voltage reversal.…”
supporting
confidence: 85%
“…Quite dramatically, a sign change occurs [15] in V SGE at a particular value of µ, and has been attributed to a Lifshitz transition, where the d xz , d yz bands originating from the Ti t 2g orbitals start to be filled. Moreover, the effect strongly depends on temperature and on the number of LAO layers in the LAO/STO heterostructure [16]. In Fig.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Therefore, the STO/LAO heterostructure can enable potential spintronic innovations and now is attracting rising research interests. [8][9][10][11][12][13] Experimentally, Narayanapillai et al 8 have reported an extremely strong charge current induced Rashba field in the 2DEG layer, which verifies the presence of strong Rashba SOC predicted at the STO/LAO interface. Most recently, the inverse Edelstein effect at the STO/LAO interface has been demonstrated by using the spin pumping technique, [10][11][12] which shows a notable spin-to-charge conversion.…”
mentioning
confidence: 85%
“…As an in-plane radio-frequency (rf) current (IRF) is applied in the STO/LAO 2DEG layer, non-equilibrium spins are generated due to the Rashba-Edelstein effect. [10][11][12]23,24 Subsequently, these spins are absorbed by the CFB layer and exert oscillating damping-like torque (DL) and/or a field-like torque (FL) on the CFB local magnetization. In addition, the rf current induces Oersted field (HRF) torque (Oe).…”
mentioning
confidence: 99%